Synthesis of low vacancies PB with high electrochemical performance using a facile method. (14th October 2020) - Chen, Yuncai; Woo, H.J.; Kufian, M.Z.; Teo, L.P.; Wang, Fei; Zhao, Changhui; Arof, A.K.
ABSTRACT: The introduction of electric vehicles (EVs) into the automotive market has boosted the advancement of energy storage technology. Although lithium-ion batteries (LIBs) could provide a solution to the emerging EV market, it needs to overcome the issue of high material cost and limited resources. This leads the research direction to sodium-ion batteries (SIBs), the most potential alternative batteries with infinite sodium resource from the ocean and earth crust. In the current work, Prussian blue (PB) with a crystal structure of face-centered cubic is used as cathode material for rechargeable SIBs with PB size ranging from 0.5 μm to 1 μm. Low interstitial water and low vacancies PB (Na0.58 Fe[Fe(CN)6 ]0.93 γ0.07 ·1.67H2 O) with high purity has been successfully synthesized at room temperature via a simple single iron source precipitation method. An excellent electrochemical performance has been shown with specific discharge capacity of 133 mAh g −1 and with 90% capacity retention over 200 cycles.